Case Study : Cleanhero (M) Sdn Bhd / Hanisah Norazam - Norazam, Hanisah (2020)
This case study has been conducted to help student in applying their knowledge about technology entrepreneurship into the real life situation where they will need to give an alternative solution to the company that has been chosen. Moreover, this case study is an opportunity for the students to experience a case study for actual business activity especially for the statistic student. We were lucky to have the chance to interview the owner of CleanHero (M) Sdn Bhd which is a professional carpet and upholstery cleaning and specialized hygiene with microbial control company. Before the actual case study is done, we had done some research on the articles that related to cleaning services so that we can get information and ideas about cleaning industry. Then, we collect information by telephone interview and observation of the chosen company. Based on the interview, we get all the information about the company such as company background, organizational structure, product or services, business marketing strategy, operational strategy, and the technology used in the company. In addition, we had identified the company strengths, weaknesses, opportunities, and threats by SWOT analysis during the interview session. From the SWOT analysis, we had discovered the problems that the company faced. The problems are limited equipment especially during certain season, lack of manpower and the competitors from the same line. These problems need to be solved to maintain their productivity and efficiency. Next, we have recommended some alternative solutions for the problems that the company faced. These alternatives will help the company and can be practiced for the purpose of business progress. Hence, this case study will explain more about the technology solutions that is possible to develop for CleanHero (M) Sdn Bhd.